Dietary supplementation with eicosapentaenoic acid in patients with schizophrenia : neuropsychological evaluation of cognitive functioning - Dippenaar, Henda (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2002.